Pengaruh Metode Latihan Drop Set dan Pyramid Set dengan Teknik Flat Bench Press terhadap Kekuatan Otot Dada pada Member Fitnes - Made Ananda Dwi Prasetya Putra; I Wayan Muliarta; Made Agus Dharmadi (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
This study aimed to determine the effect of drop set and pyramid set resistance training methods using the flat bench press technique on improving chest muscle strength among male fitness members at Rai Fitness, Badung Regency, Bali, and to identify the more effective training method. This research employed a quasi-experimental pretest–posttest control group design. The sample consisted of 45 male fitness members aged 18–30 years, divided into three groups: drop set, pyramid set, and control groups. The training intervention was conducted for eight weeks with a frequency of three sessions per week. Chest muscle strength was measured using the one-repetition maximum (1RM) flat bench press test before and after the intervention. Data were analyzed using normality tests, homogeneity tests, paired-sample t-tests, and independent-sample t-tests. The findings indicated that both drop set and pyramid set training methods significantly improved chest muscle strength across all age, height, and body weight categories. However, the drop set method produced a greater average increase in chest muscle strength compared to the pyramid set method. Statistical analysis revealed a significant difference in effectiveness between the two methods, with the drop set method demonstrating superior outcomes. This superiority is attributed to training performed until maximal fatigue, which stimulates greater neuromuscular adaptation and muscle hypertrophy. Both training methods are effective in enhancing chest muscle strength; however, the drop set method is more effective and is recommended as the primary training strategy for achieving rapid and significant strength gains. The pyramid set method remains a valuable alternative for progressive strength development with controlled intensity. Training programs should be tailored to individual characteristics to ensure safety, effectiveness, and optimal outcomes.